2021
DOI: 10.3390/jof7060413
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Profiling Identified Transcription Factors, Biological Process, and Associated Pathways for Pre-Harvest Aflatoxin Contamination in Groundnut

Abstract: Pre-harvest aflatoxin contamination (PAC) in groundnut is a serious quality concern globally, and drought stress before harvest further exacerbate its intensity, leading to the deterioration of produce quality. Understanding the host–pathogen interaction and identifying the candidate genes responsible for resistance to PAC will provide insights into the defense mechanism of the groundnut. In this context, about 971.63 million reads have been generated from 16 RNA samples under controlled and Aspergillus flavus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…ABR17 is a member of the group 10 family of pathogenesis-related proteins (PR 10), Srivastava et al (2006) found that ABR17 from pea confers multiple stress tolerance in A. thaliana. ABR17 from peanut also regulates the genes for ABA responsive elements during drought stress, providing resistance against Aspergillus flavus infection (Soni et al 2021). As a critical plant hormone, we will further research ABA and its related genes in our future work.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ABR17 is a member of the group 10 family of pathogenesis-related proteins (PR 10), Srivastava et al (2006) found that ABR17 from pea confers multiple stress tolerance in A. thaliana. ABR17 from peanut also regulates the genes for ABA responsive elements during drought stress, providing resistance against Aspergillus flavus infection (Soni et al 2021). As a critical plant hormone, we will further research ABA and its related genes in our future work.…”
Section: Discussionmentioning
confidence: 98%
“…ABR17 from peanut also regulates the genes for ABA responsive elements during drought stress, providing resistance against Aspergillus flavus infection (Soni et al . 2021). As a critical plant hormone, we will further research ABA and its related genes in our future work.…”
Section: Discussionmentioning
confidence: 99%
“…The unique transcripts were obtained after removing the low number of reads from the raw data. We annotated all unigenes against a full set of BLAST searches to find the most descriptive annotations, including the NR ( e -value = 1e-5), NT ( e -value = 1e-5), KOG ( e -value = 1e-3), PFAM ( e -value = 0.01), Swiss-Prot ( e -value = 1e-5), ITAK (TF prediction software based on hmmscan) ( Soni et al, 2021 ), Gene Ontology (GO) ( e -value = 1e-6), and Kyoto Encyclopedia of Genes and Genomes (KEGG) ( e -value = 1e-10) database. To calculate and normalize the transcript abundance of the unigenes in each sample, the FPKM method was adopted ( Li and Dewey, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…In general, pre-and post-harvest contamination are two major types caused by A. flavus (Guo et al, 2008a(Guo et al, ,b, 2011Liao et al, 2009;Wang et al, 2013;Clevenger et al, 2016;Zhao et al, 2019;Soni et al, 2021). Two types of mechanism for host resistance to A. flavus, in vitro seed colonization and aflatoxin production, have been documented, which were further proved to be independently inherited (Liao et al, 2009;Nigam et al, 2009;Pandey et al, 2019;Soni et al, 2020), thus making it a great challenge for the researchers to elucidate resistance mechanism, breed resistant lines, and eventually control the disease in peanuts.…”
Section: Introductionmentioning
confidence: 99%